The art of discovering and exploiting unexpected opportunities: The roles of organizational improvisation and serendipity in new venture performance - Fultz, Andrew E.F.; Hmieleski, Keith M. (Journal of Business Venturing, 2021)
This study examines a model linking organizational improvisation with new venture performance, via serendipity, at varying levels of resource constraints and informal organizational structure. Results from a national sample of 326 startups, based throughout the United States, indicate that the association of improvisation with serendipity is greatest when resource constraints are high, and—in turn—that serendipity is positively related to new venture performance when informal organizational structure is high. These findings highlight novel pathways and contingencies through which improvisation may prove to be a resourceful means for startups to identify new opportunities and gain performance advantages.